The debate on philosophical sufism: Dynamics and dialectics in Aceh - Mukhlis Latif (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
This research aims to explain the philosophy of tasawuf Hamzah Fansri in Nusantara Islam. The textual research method was employed to interpret the contents in the manuscripts of tasawuf falsafi in Aceh, especially regarding tasawuf falsafi, which Hamzah Fansūrī developed. The study findings confirm that Hamza Fansūrī's philosophical tasawuf thought is